(untitled) (Journal of Academic Research, 2026)
Background: Cancer patients are highly susceptible to microbial infections, particularly those caused by multidrug-resistant (MDR) hospital-acquired bacteria. Such infections pose a serious threat to immunocompromised individuals and complicate treatment decisions. Understanding the epidemiology of these pathogens and their antibiotic susceptibility patterns is therefore essential for improving patient outcomes. This study aimed to identify microorganisms isolated from venous and urinary catheters in cancer patients and evaluate their susceptibility to commonly used antibiotics. Methods: Catheter tip samples were collected from patients at the National Cancer Institute, representing both genders and a wide age range. Samples were cultured on Blood agar, MacConkey agar, and Chocolate agar, then incubated at 37°C for 24–48 hours. Bacterial identification was performed using Gram staining, catalase and coagulase tests for Gram-positive species, and biochemical tests and API 20E for Gram-negative species. Antibiotic susceptibility testing followed Clinical and Laboratory Standards Institute (CLSI) guidelines using routinely used antibiotics. Results: Of 56 catheter samples (central lines: 28; Port-a-caths: 10; urinary catheters: 18), microbial growth was detected in 83.9%. Bacterial isolates represented 83.9% of positive samples, while fungal isolates accounted for 16.1%. Gram-positive bacteria were more common (58.1%) than Gram-negative (25.8%). Staphylococcus aureus (38.8%) was the predominant Gram-positive isolate, followed by Streptococcus spp. (9.6%), Bacillus spp. (6.5%), and Enterococcus faecalis (3.2%). Among Gram-negative bacteria, Klebsiella pneumoniae (12.9%) was most frequent, followed by Pseudomonas aeruginosa (6.5%), Serratia marcescens (3.2%), and Acinetobacter spp. (3.2%). S. aureus isolates showed high susceptibility to amikacin, imipenem, and ciprofloxacin, while K. pneumoniae isolates were largely susceptible to ciprofloxacin and meropenem. Conclusion: The findings demonstrate clear differences in antibiotic susceptibility between Gram-positive and Gram-negative pathogens. Further research should investigate biofilm formation, which may reduce antibiotic efficacy.